Analisis Dinamis Hubungan Antara Harga Saham dan Variabel Makroekonomi - Paulina Harun (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Previous research has proven the influence between interest rates, inflation, exchange rate, trade balance, industrial production index on stock prices. By using the Autoregressive Distributed Lag (ARDL) model approach and the 13 companies listed on the IDX, in this study, we will look deeper into the dynamics of long-term and short-term relationships for the aforementioned variables. The research period starts from January 2015 to December 2019, during which time there were many global upheavals that had a considerable impact on the Indonesian economy, through the ARDL model of interest rates, inflation, exchange rate, trade balance, industrial production index, and stock prices are proven to have long-term cointegration or move together in the long term. But not only in the long run, but these seven variables also have a dynamic short-term relationship that has a sufficient speed of adjustment towards equilibrium per month.